Novel 3-DOF counterbalance mechanism based on spring balancer for mobile robot arms. (April 2022) - Lee, Won-Bum; Kim, Do-Won; Song, Jae-Bok
Abstract: Mobile robot arms have been recently used in service sites. However, their payload is usually small due to the limitation of battery capacity, making it difficult to perform various tasks. Counterbalance mechanism (CBM), a mechanical device that compensates for gravitational torque or force acting on the robot, is one of the good solutions to this payload limit. However, conventional CBMs are focused only on revolute joints, so their application to mobile robot arms possessing a prismatic joint is limited. Therefore, we propose a 3-DOF CBM that counterbalances a robot with prismatic–pitch–pitch joints utilizing only one spring balancer. One prismatic joint and two pitch joints are counterbalanced through a single wire, which is subjected to a constant restoring force generated by a base-mounted spring balancer, and each link of the CBM is only equipped with small idlers. Thanks to this unique structure of the proposed 3-DOF CBM, its application to mobile robot arms can efficiently enhance the payload performance with a minimal increase in volume and mechanical complexity. The experiments confirmed that the proposed CBM and the mobile robot arm equipped with it can properly counterbalance all joints of the arm.